2009
DOI: 10.1021/ja9061163
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Synthetic Polyamines for Controlled Biomimetic Silica Formation

Abstract: Organic compounds isolated from diatoms contain long-chain polyamines with a propylamine backbone and variable methylation levels and chain lengths. These long-chain polyamines are thought to be one of the important classes of molecules that are responsible for the formation of the hierarchically structured silica-based cell walls of diatoms. Here we describe a synthetic route based on solid-phase peptide synthesis from which well-defined long-chain polyamines with different chain lengths, methylation patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 50 publications
0
93
0
1
Order By: Relevance
“…This encapsulation would afford the LCPAs physical protection so long as the silica remains. In-vitro experiments have recently shown that natural and synthetic LCPAs (along with silaffins) induce silica precipi- tation when added to a metastable solution of monosilicic acid (Krö ger et al, 2000;Noll et al, 2002;Bernecker et al, 2010). The protonated amino groups of LCPAs may serve as binding sites for silicic acid (Coradin et al, 2002).…”
Section: Oceanographic Significancementioning
confidence: 99%
“…This encapsulation would afford the LCPAs physical protection so long as the silica remains. In-vitro experiments have recently shown that natural and synthetic LCPAs (along with silaffins) induce silica precipi- tation when added to a metastable solution of monosilicic acid (Krö ger et al, 2000;Noll et al, 2002;Bernecker et al, 2010). The protonated amino groups of LCPAs may serve as binding sites for silicic acid (Coradin et al, 2002).…”
Section: Oceanographic Significancementioning
confidence: 99%
“…[1][2][3][4][5][6] For the TEM analysis of specimens dispersed in liquids, samples are conventionally dried from suspension onto a 30-50 nm carbon or polymer covered metal grid. For organic materials, which are relatively transparent to the electron beam, drying is oen combined with negative staining to generate contrast.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional syntheses of silica-based materials require elevated temperature, high pressure, strongly acidic or alkaline media, and a long time for the synthesis process [6]. By comparison, biologically controlled silica materials production not only occurs under benign conditions but also produces silica materials with hierarchically ordered pore structures ranging from the nanometer to micrometer domain [7,8]. Such materials can provide a high specific surface area and more interaction sites via nanopores, while the presence of additional macropores can enhance mass transport and easier accessibility to the active sites.…”
Section: Introductionmentioning
confidence: 99%